Deteksi Serangan Distributed Denia of Services (DDOS) Berbasis HTTP Menggunakan Metode Fuzzy Sugeno - Nadila Sugianti; Yayang Galuh; Salma Fatia; Khadijah Fahmi Hayati Holle (JISKA (Jurnal Informatika Sunan Kalijaga), 2020)
Distributed Denial of Services (DDOS) is a type of attack that exploits the web. This attack causes the server to go down and a system error. Thus, early detection of DDOS attacks is fundamental. The purpose of this paper is to develop applications that are capable of detecting HTTP-based DDOS attacks. This paper uses the sugeno fuzzy method for a systematic approach. From several studies that have been conducted, the researchers identified that the optimal input variables included the number of users, number of packages, number of lengths / users, and length of packages. Data processing used MATLAB software. The validity of the test uses the formula for the level of accuracy as in equation (3), resulting in an application that is able to detect HTTP-based DDOS attacks using sugeno fuzzy method with an accuracy rate of up to 90%.